Trabecular anisotropy and collagen fibre orientation in the mandibular condyle following experimental functional appliance treatment using sheep - Ma, B.; Sampson, W. J.; Wiebkin, O. W.; Wilson, D. F.; Fazzalari, N. L. (Veterinary and Comparative Orthopaedics and Traumatology, 2006)
In order to study the modifying effects of functional appliances on the mechanical environment of the temporomandibular joint (TMJ), we characterised the structure of the mandibular condyle subsequent to an experimental functional appliance intervention. Eight, four-month-old, castrated male Merino sheep, were randomly allocated to experimental and control groups (n = 4 in each group). Forward mandibular displacement was induced with an intraoral appliance. The study period was 15 weeks, during which time fluorochromes were administered to all of the animals. Midsagittal sections of the TMJ were selected for analysis and trabecular anisotropy was estimated using bone histomorphometry. Only the experimental group demonstrated that the trabecular bone in the central condylar region was less anisotropic when compared to the subchondral region. Also, the variation in trabecular anisotropy of the central condylar region was found to be smaller in the experimental group. The collagen fibre orientation was analysed under polarised light as the proportion of the dark or bright fibres observed in regions which existed before, and regions which formed during the experiment, as determined by the fluorochrome labels. In the experimental group, more bright collagen fibres were found in the most superior region of the mandibular condyle when compared with the controls. These results suggested that the experimental functional appliances changed the orientation and pattern of the mechanical forces acting on the mandibular condyle, and possibly increased the magnitude of the lateral functional forces applied to the most superior part of the condyle during such treatments.
Keywords: Sheep mandibular condyle; growth modification; collagen fibre orientation; trabecular anisotropy